2017
DOI: 10.47203/ijch.2017.v29i04.013
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Behaviors Related Factors of Senior High Schools Teenagers in Bukittinggi 2017

Abstract: Background: The increasing number of the teenager’s sexual behavior in Indonesia is influenced by many factors. The purpose of this study was to determine factors associated with sexual behavior of Senior High Schools in Bukittinggi. Aims & Objectives: This study is aimed to determine the factors which are associated with the sexual behavior of high school teenagers in Bukittinggi. Material & Methods: This study was a correlation study with the simple random sampling of 360 adolescent. This research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In line with this observation, a study based on Pokhara Metropolitan observed that 85.09% of the students had their sexual experience between the age of 15-19 years, while 10.56% were sexually active before the age of 15 and 13.33% adolescents had unprotected sex. 19 Similarly, the initiation of sexual engagement before the age of 18 and unprotected sex has been reported by multiple studies from Nepal. 20, 21 Likewise, a study from rural Nepal also reported that 28.2% of the sexually active youth were engaged with multiple sexual partners.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In line with this observation, a study based on Pokhara Metropolitan observed that 85.09% of the students had their sexual experience between the age of 15-19 years, while 10.56% were sexually active before the age of 15 and 13.33% adolescents had unprotected sex. 19 Similarly, the initiation of sexual engagement before the age of 18 and unprotected sex has been reported by multiple studies from Nepal. 20, 21 Likewise, a study from rural Nepal also reported that 28.2% of the sexually active youth were engaged with multiple sexual partners.…”
Section: Discussionmentioning
confidence: 63%
“…22 The sexual engagement of students with commercial sex works has also been reported by numerous studies from Nepal where it is expected to range between 8.5% and 48.9%. 11, 1921, 23 Despite presence of laws and programs aimed to prevent minors’ engagement in sexual activities to protect them from sexual abuse, as well as regulations controlling commercial sex work and various initiatives focusing on adolescent sexual and reproductive health, these risky behaviors persist. This underscores the urgent necessity for more effective and comprehensive sexual education interventions among Nepalese adolescents and youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation